1993
DOI: 10.1007/bf00371599
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 antigen expression and growth pattern of basal cell carcinomas

Abstract: The expression and location of the Ki-67 antigen was investigated in 62 basal cell carcinomas (BCC) using immunostaining techniques (PAP and APAAP) on cryostat sections. The tumor samples were classified into three groups according to microarchitecture (nodular, superficial or fibrosing). The Ki-67 growth fraction displayed great variation between tumors belonging to the same group (nodular type, 7-67%; superficial type, 18-49%; fibrosing type 4-33%). In nodular and superficial BCC formations Ki-67 reactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
2
17
1
Order By: Relevance
“…17 It is still unknown what signals determine the extent of proliferative activity in BCCs. 28 Our findings indicate that VDR expression is not exclusively a function of cellular proliferation in these tumor cells, but may be determined by additional, different mechanisms.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…17 It is still unknown what signals determine the extent of proliferative activity in BCCs. 28 Our findings indicate that VDR expression is not exclusively a function of cellular proliferation in these tumor cells, but may be determined by additional, different mechanisms.…”
Section: Discussionmentioning
confidence: 70%
“…Our findings are in agreement with previous immunohistochemical investigations that have demonstrated peripheral or random distribution of Ki-67-positive cells in BCCs of all different histological types. 28 The actual pro- liferative rate of BCC cells is somewhat unclear, but it appears to be in the range of that of normal keratinocytes. 17 It is still unknown what signals determine the extent of proliferative activity in BCCs.…”
Section: Discussionmentioning
confidence: 99%
“…It is not in line with the clinical finding that it is usually a slow-growing and indolent neoplasia with minimal metastatic potential (Tilli et al 2005). This phenomenon could be explained either by a prolonged duration of the cell cycle, or a considerable and continual loss of cells accompanied by their permanent renewal (Baum et al 1993). Already in 1972, Kerr & Searle (1972) supposed that a seemingly paradoxically slow growth rate of BCC might be due to a high apoptotic rate of tumor cells.…”
Section: Discussionmentioning
confidence: 91%
“…This observation raises the possibility that it may have partly different impact on evolution and biological behavior of this neoplasia. Moreover, the vast majority of the authors (Baum et al 1993;Al-Sader et al 1996;Horlock et al 1997;Lee et al 2000;Tilli et al 2002;Mazzarelli et al 2003;Ionescu et al 2006) found that Ki-67 growth fraction varied considerably between different histomorphological BCC types, even in the tumors belonging to the same group. Our results have shown a wide percentage range in each histological BCC type as well, regardless whether they were primary or recurrent lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation